1984
DOI: 10.3109/02844318409052855
|View full text |Cite
|
Sign up to set email alerts
|

Experience with the Radial Forearm Flap in 14 Cases

Abstract: In 14 cases aged 9-79 years the radial forearm flap has been used for reconstruction. Of 4 island flaps, 2 were distally based (1 with nerve anastomosis) and 2 proximally based (1 innervated). Of the free flaps, 7 were for intra-oral lining following major resection and 3 of these included hemi-radius for mandibular reconstruction. Most flaps were put into a hostile environment resulting from chronic infection and/or radiotherapy or fast neutron therapy. Two flaps failed including one osseocutaneous free flap.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
14
0

Year Published

1989
1989
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 10 publications
0
14
0
Order By: Relevance
“…[1][2][3]13,15 Early reports of its use identify a history of such complications. 2,[20][21][22] In a series of 14 radial forearm flaps, Matthews et al 21 emphasized that venous congestion was more marked in cases that relied on retrograde venous flow. Soutar and Tanner 2 encountered venous congestion in a reverse flow flap that led to necrosis and delayed primary healing, which he salvaged by anastomosis of the cephalic vein to a dorsal hand vein.…”
Section: Discussionmentioning
confidence: 98%
“…[1][2][3]13,15 Early reports of its use identify a history of such complications. 2,[20][21][22] In a series of 14 radial forearm flaps, Matthews et al 21 emphasized that venous congestion was more marked in cases that relied on retrograde venous flow. Soutar and Tanner 2 encountered venous congestion in a reverse flow flap that led to necrosis and delayed primary healing, which he salvaged by anastomosis of the cephalic vein to a dorsal hand vein.…”
Section: Discussionmentioning
confidence: 98%
“…Early published series demonstrated donor radius fracture rates ranging up to 67%. 6 In 1999, Thoma et al reported a 15% fracture incidence in 60 consecutive patients over a 11-year period. 15 Many of these arms were prophylactically immobilized, and fractures were treated with a variety of methods ranging from prolonged immobilization to vascularized bone graft reconstructions.…”
Section: Discussionmentioning
confidence: 99%
“…Two issues have been largely to blame for limiting surgeons' consideration of the OCRFFF as an option for single-stage reconstruction of composite defects in the head and neck: the inadequacy of available bone and the potential for morbidity, most notably pathological fracture. 6,7 INDICATIONS AND CONTRAINDICATIONS We describe a modified harvest technique for the OCRFFF that employs prophylactic internal fixation of the donor radius. The evolution of this technique has resulted in a safe OCRFFF harvest, with donor site morbidity similar to that observed with the widely used RFFF.…”
mentioning
confidence: 99%
“…[1][2][3][4][5][6] Its use historically has been limited by the purportedly high rate of donor radius fracture. Matthews et al 7 in 1983 reported a rate of 67 percent when two of three of their initial radial osteocutaneous free flaps had donor radius fractures after resection of 50 percent of the diameter of the radius through perpendicular osteotomies. Donor radius fracture is considered the greatest disadvantage of the flap, as several studies have reported severe functional impairment after fracture.…”
mentioning
confidence: 99%